Enhanced Design and Analysis of the Microcantilever-Based Bio-Sensor to Detect Carcinoembryonic Antigen Tumor Biomarkers - Ibrahimi, Khalid Mohd; Kumar, Rajagopal; Pakhira, Writtick; Panwala, Fenil C. (Computer Assisted Methods in Engineering and Science, 2023)
Frequently, early detection of a malignant condition prevents most premature deaths. In this paper, three new designs are proposed for the microcantilever-based biosensor to detect carcinoembryonic antigen (CEA) tumor biomarkers. CEA is used for several types of human cancers, e.g., lung cancer, pancreatic cancer, breast cancer, ovarian cancer, and gastric cancer, particularly colorectal cancer. The proposed models are designed and the finite element method (FEM) analysis of these biosensors is performed using a COMSOL 5.4 Multiphysics (commercial package) software. Various analyses and comparisons are carried out by utilizing the designs in terms of displacement as well as piezo-resistive output due to an increase in mass of CEA adsorbed onto the surface of the cantilever beam, which is stimulated by applying a pressure range of 0 to 0.2 Pa on to the surface of a cantilever beam. A simulation is performed with the proposed designs by experimenting with different materials for better deflection results. Regarding the results obtained, Design 3, made with Kynar710, gives the highest total deflection of 0.7328 µm. However, a piezo-resistive readout technique is utilized to get the output in mV, and for that, p-silicon (single-crystal, lightly doped) material is used, respectively. Next, 5V is applied to the terminals of the piezo-resistive circuit. Based on the input applied pressure and output mV, the Design 3 made with Kynar710 gives a better sensitivity of 0.13089 [mV/V/Pa] compared to other designs made with other materials.